TEKNOLOGI PEMOTONG RANTING ADJUSTABLE DENGAN SISTEM HIDROLIK MINI - Zufri Hasrudy Siregar (Universitas Quality, 2018)
This research is the creation of a simple new technology by manipulating the hydraulic system and the principle of hand grip that functioned as an ergonomically adjustable twistable short cutter, with a normal length of 1.5 meters, a maximum of 3 meters. Weight 2.8 kg, long grasp of 94 mm and the diameter of the handle 52 mm. This research uses ergonomic analysis method to know suitability of tool with human that is with taking 95 percentile. At the diameter of the hand grip 54, 29 mm while for the width of the palm of the hand is 97.87 mm, the maximum pressure required to cut the twig is 234.39 kg / cm2 with a diameter of 5 mm that is the type of twig cocoa. While the NIOSH analysis obtained the required weight is 4.89 kg, then with the QEC method obtained the highest percentage level of the score is 47.62. it means repair is needed for the tool in the future. For the loading of work so as not to tired with working time of 8.40 minutes and rest 7.14 minutes. The results of the study concluded that the tool still has to be repaired in the future, while its use is quite short and only functioned for clove planting only and other similar harvesting with a maximum diameter (1 cm) only.